Processability and tensile performance of continuous glass fiber/polyamide laminates for structural load-bearing applications. (February 2018) - Nikforooz, M.; Golzar, M.; Shokrieh, M.M.; Montesano, J.
Abstract: The performance of continuous E-glass/polyamide 6 laminates processed using distinct hot press moulding cycles was assessed and compared with similar E-glass/epoxy and E-glass/polypropylene laminates. The effects of peak processing temperature, preheating time, and temperature dwell time on laminate consolidation and quality were observed using optical and scanning electron microscopy. Corresponding quasi-static tensile tests were performed on [0]8, [90]8, [02 /902 ]s, [04 /904 ]s and [±45]2s laminates. Compared to E-glass/epoxy composites, the [0]8 specimens presented a similar strength, while the [90]8 specimens exhibited a much lower strength due to weaker fiber/matrix adhesion. Conversely, the E-glass/polyamide cross-ply laminates had a markedly higher strength while exhibiting the same modulus. This is because of higher toughness; the polyamide matrix provides as was proved by higher transverse matrix cracking strain of E-glass/polyamide. These findings support the feasibility of producing cost-effective and high-quality E-glass/polyamide laminates for use in high-performance applications, which is an attractive alternative to more conventional glass/epoxy laminates.